Usyur Sebagai Instrumen Pemasukan Negara dan Peningkatan Kesejahteraan Ekonomi Islam - Na’im, Fairuz ‘Ainun; Janwari, Yadi; Alhakim, Sofian (MASILE, 2025)
In Islamic economics, usyur is one of the state's fiscal policy instruments, which contributes to increasing national revenue and public welfare by imposing customs duties on products imported into the country. This study is a library study that adopts an explanatory and descriptive research approach. The methods used to process the research data are primary and secondary source review and library/document research through data reduction, data presentation, and conclusion stages. The results of this study indicate that usyur is one of the fiscal policy instruments of Umar ibn Khattab's Ijtihad and is very important and plays a role in increasing national income through non-Zakat revenue. Ushr plays an important role in the Islamic economy, serving as a source of state revenue, monitoring and controlling goods imported into the country, and maintaining economic stability by imposing customs duties on goods to achieve the public interest. are doing.